2008
DOI: 10.1111/j.1365-2044.2008.05574.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the utility of pre‐operative brain natriuretic peptide in predicting early and intermediate‐term mortality and major adverse cardiac events in vascular surgical patients

Abstract: SummaryWe conducted a meta-analysis of the utility of pre-operative B-type natriuretic peptide (BNP) and N-terminal-pro B-type natriuretic peptide in predicting early (< 30 days) and intermediate (< 180 days) term mortality and major adverse cardiac events (cardiac death and nonfatal myocardial infarction) in patients following vascular surgery. A Pubmed Central and EMBASE search was conducted up to January 2008. Of 81 studies identified, seven prospective observational studies were included in the meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 27 publications
6
74
0
4
Order By: Relevance
“…[9] The current data on BNP for preoperative risk assessment fulfil proof of concept for cardiovascular complications, [10,11] validation in prospective studies, [12,13] incremental value by significantly improving the revised cardiac risk index's prediction of major adverse cardiac events, [14] and clinical utility through a significant improvement in preoperative risk classification. [15] Importantly, the fifth stage of integration of a biomarker into clinical practice demands demonstration that biomarker-directed therapy improves clinical outcome.…”
Section: Priority 2 a Randomised Controlled Trial Of Preoperative B-mentioning
confidence: 90%
“…[9] The current data on BNP for preoperative risk assessment fulfil proof of concept for cardiovascular complications, [10,11] validation in prospective studies, [12,13] incremental value by significantly improving the revised cardiac risk index's prediction of major adverse cardiac events, [14] and clinical utility through a significant improvement in preoperative risk classification. [15] Importantly, the fifth stage of integration of a biomarker into clinical practice demands demonstration that biomarker-directed therapy improves clinical outcome.…”
Section: Priority 2 a Randomised Controlled Trial Of Preoperative B-mentioning
confidence: 90%
“…This finding was similar to a study by Schutt et al, who observed increased preoperative NT-proBNP but not postoperative NT-proBNP levels were associated with postoperative cardiac events; however, increased postoperative levels of NT-proBNP were common in all patients [43]. There are several meta-analyses and systematic reviews of studies evaluating BNPs in the surgical population; and they consistently demonstrate that BNPs, in particular when drawn preoperation compared with postoperation, are independent predictors of both short-and long-term adverse cardiac events, including cardiac deaths and all-cause mortality [143,144]. In addition, BNPs were found to be useful as a stratification tool to assess risk for postoperative cardiovascular complications [145].…”
Section: Brain Natriuretic Peptides As a Marker Of Cardiovascular Rismentioning
confidence: 99%
“…In addition, BNPs were found to be useful as a stratification tool to assess risk for postoperative cardiovascular complications [145]. A meta-analysis of vascular surgery patients found that increased preoperative BNP levels (including NT-proBNP) were associated with increased risk of 30-day postoperative cardiac events, cardiac-related mortality and all-cause deaths up to 180 days [144]. Using preoperative BNPs significantly improved the preoperative predictive risk classification of the traditionally utilized RCRI [145].…”
Section: Brain Natriuretic Peptides As a Marker Of Cardiovascular Rismentioning
confidence: 99%
“…Almost uniformly every study conducted in non-cardiac surgical populations has reported that preoperative NP measurement elevations are predictive of short (≤ 30 day), intermediate (>30-180 day) and long-term (>180 day) postoperative mortality, 4 as well as major adverse cardiac events such as myocardial infarction, troponin elevation, cardiac failure, and atrial fibrillation. This signal has been repeatedly demonstrated in multiple meta-analyses.…”
Section: Introductionmentioning
confidence: 99%